VD_FINDINFO Jug / 2019 / 157 vom 30. August 2018 - VD Tribunal cantonal (2018)
DROIT DE LA FONCTION PUBLIQUE, STAGE, REFUS DE STATUER | 29 Cst., 1 al. 1 LPers-VD, 14 LPers-VD, 16 LPers-VD, 2 al. 1 LPers-VD, 155 RLPers-VD, 310 CPC (CH), 3a LHC